De novo and secondary anaplastic meningiomas: a study of clinical and histomolecular prognostic factors. Issue 8 (5th December 2017) - Peyre, Matthieu; Gauchotte, Guillaume; Giry, Marine; Froehlich, Sébastien; Pallud, Johan; Graillon, Thomas; Bielle, Franck; Cazals-Hatem, Dominique; Varlet, Pascale; Figarella-Branger, Dominique; Loiseau, Hugues; Kalamarides, Michel
Abstract: Background: Following recent studies underlining the differences between de novo and secondary anaplastic meningiomas and the prognostic value of telomerase reverse transcriptase ( TERT ) promoter mutation, we decided to conduct a multicenter retrospective study to address these questions and determine specific prognostic factors in each of these 2 anaplastic meningioma subgroups. Methods: Among the 68 meningioma cases initially selected, only 57 were confirmed as anaplastic meningiomas after centralized pathological review. TERT promoter mutation analysis was performed in all cases. Results: Median overall survival was 2.6 years and 5-year survival rate was 10%. This study confirmed the better prognosis of de novo anaplastic meningiomas (28 tumors) compared with secondary anaplastic meningiomas (29 tumors) ( P = 0.02). In the "de novo" group, meningiomas diagnosed on histological anaplasia alone had a better prognosis than those in patients with a high number of mitoses with or without anaplasia ( P = 0.01). In the "secondary" group, tumors demonstrate very heterogeneous clinical courses leading to malignant transformation, and time to first relapse as a low-grade tumor was a strong predictor of overall survival ( P = 0.0007). TERT promoter mutation in anaplastic meningiomas was rare (14%) and did not influence overall survival but was associated with a shorter recurrence-free survival in the secondary anaplastic meningioma subgroup ( P = 0.02). The absence of TERT promoter methylation, although rare (3/33 cases), may be associated with prolonged overall survival ( P = 0.02). Conclusion: This study highlights the different prognoses of de novo and secondary anaplastic meningiomas with specific prognostic factors in each subgroup. The analysis of TERT mutation and methylation could provide additional prognostic insights.